An Analysis of Steel Material Inventory Management Using the Just-in-Time (JIT) Approach: A Case Study at PT XYZ - Indrawan, Beni; Ludiya, Eka; Rahardianto, Rahardianto (Darul Yasin Al Sys, 2025)
This study investigates the problem of excessive raw material inventory at PT XYZ, driven by a misalignment between procurement planning and actual production demand, which has led to higher storage costs and operational inefficiencies. The research aims to analyze the root causes of inventory control issues and design an optimized inventory management system using the Just-In-Time (JIT) approach. A qualitative methodology with a social situation framework was applied, incorporating direct observations, in-depth interviews with warehouse managers and staff, and secondary document analysis. Triangulation techniques were used to ensure data credibility and reliability. Findings indicate that JIT implementation reduces inventory excess, optimizes storage utilization, strengthens coordination between departments and suppliers, lowers unnecessary costs, and improves service quality. The study contributes to the understanding of JIT application in the automotive industry, with novelty demonstrated through PT XYZ’s shift from traditional inventory methods to JIT. The research concludes that JIT is an effective solution for addressing inventory control challenges and suggests that its adoption could serve as a model for other manufacturing firms seeking to enhance inventory efficiency and competitiveness.